2014
DOI: 10.1007/s10461-014-0817-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Shaping Initial Decision-Making to Self-test Amongst Cohabiting Couples in Urban Blantyre, Malawi

Abstract: In sub-Saharan Africa, most new HIV infections occur in stable relationships, making couples testing an important intervention for HIV prevention. We explored factors shaping the decision-making of cohabiting couples who opted to self-test in Blantyre, Malawi. Thirty-four self-tested participants (17 couples) were interviewed. Motivators for HIV self-testing (HIVST) emerged at three main levels. Individual motivations included perceived benefits of access to treatment, and self-checking of serostatus in the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(113 citation statements)
references
References 39 publications
5
108
0
Order By: Relevance
“…However, in relationships where women did not communicate regularly about health issues with their male partners, including in situations where the male partners were not usually around in the home, there were delays in delivering the kits. These observations suggest that partner communication is an important element in enhancing the delivery and eventual use of HIVST kits by male partners [21,22]. However, some of the tactics used by the women, especially the misinformation and failure to provide accurate information, could be potentially detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…However, in relationships where women did not communicate regularly about health issues with their male partners, including in situations where the male partners were not usually around in the home, there were delays in delivering the kits. These observations suggest that partner communication is an important element in enhancing the delivery and eventual use of HIVST kits by male partners [21,22]. However, some of the tactics used by the women, especially the misinformation and failure to provide accurate information, could be potentially detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the belief that HIVST can expand testing of target populations through the freedom and opportunity to test at one's convenience, in any location [22,31,38,39] key informant stakeholders in all contexts strongly advocated the health facility route. This may have been informed by concerns regarding the lack of counselling and poor linkage to care associated with self-testing [31,40].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous paper described how the community counsellors (CC) provided HIVST to community members through a community-based model and how participants of this study were recruited [15]. This study recruited participants who self-tested within the CRT and who had no prior knowledge of the interviewers before commencement of data collection.…”
Section: Methodsmentioning
confidence: 99%
“…HIV self-testing (HIVST) is a novel HIV screening approach that involves an individual performing an HIV test and interpreting the test results in private [8] and has great potential for increasing the uptake of couples testing and reaching male partners [14, 15]. A recent couple-targeted clinical trial in Kisumu, Kenya demonstrated a high uptake of couple testing achieved through the use of oral-fluid-based HIV test kits delivered through antenatal and postpartum women [16].…”
Section: Introductionmentioning
confidence: 99%